PERAN PENYULUH PERTANIAN SWADAYA DALAM MENDUKUNG PERLINDUNGAN LAHAN PERTANIAN PANGAN BERKELANJUTAN AKIBAT PERKEMBANGAN KAWASAN SOLOBARU KABUPATEN SUKOHARJO - ARKANUDIN RIZKI PERMONO; VINCENT HADI WIYONO; LUKMAN HAKIM (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The development of the Solo Baru and Kartasura Regions provides support for the economic growth of Sukoharjo Regency and Solo City. The concept of the Solo Baru and Kartasura Regions as independent satellite cities with the concept of settlements supported by the availability of supporting facilities will impact on land use changes. Changes in land use have an impact on the agricultural sector. The existence of the agricultural sector as a provider of national food barns in Sukoharjo Regency is increasingly threatened because agricultural land has changed its function to become a non-agricultural industrial area. Farmer empowerment is an important concern to deal with these changing conditions. The involvement of farmers as independent agriculture instructors is an alternative solution for empowering farmers. This alternative solution is in accordance with Law Number 16 of 2006 concerning Agricultural, Fisheries and Forestry Extension Systems. This study aims to describe the role of independent agriculture instructors in supporting the protection of sustainable agricultural land due to the development of the New Solo Region in Sukoharjo Regency. The research method uses a qualitative descriptive approach, data collected through interviews, observation, Focus group discussions (FGD), and documentation. Self-supporting Agricultural Extension Workers have 3 (three) roles. First, the distribution of government program information to farmer group members in each sub-district. Second, strengthening the bargaining position of farmers to the government and the private sector. Third, organizing farmer groups through the management of Microfinance Institutions; farm business facilitators; and conducting farmer group visiting activities.